Perbedaan Optimisme Pada Siswa SMA NU 2 Gresik Ditinjau Dari Jenis Kelamin - Idayatul Khasanah; Muhimmatul Hasanah; Setyani Alfinuha (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Idayatul Khasanah (190701009). Differences in Optimism in Students of SMA NU 2 Gresik Reviewed by Gender. This study aims to determine the Differences in Optimism in Students of SMA NU 2 Gresik Reviewed from Gender. This study uses a quantitative approach, with a comparative method. Respondents in this study were students of SMA NU 2 Gresik. The sampling technique with nonprobability sampling using accidental sampling technique. A total of 110 respondents. The scale validity test uses content validity. Reliability test uses Alpha Cornbach. This study uses an optimism scale with a reliability of 0,885. Data analysis uses a different test, namely the independent sample t-test. The results of the hypothesis test show that the hypothesis of this study (Hₐ) is rejected because the Sig. (2-tailed) value is 0.076> 0.05. So, there is no significant difference in optimism in gender. The unproven hypothesis in this study can be caused by various factors that influence students' overall optimism. These factors include socio-economic conditions, the culture that applies in the student's environment, the area of residence (village or city), and social interaction patterns that are formed in schools and families.